2003
DOI: 10.1111/j.1365-2621.2003.tb05700.x
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Detection in Skim Milk by Electron Spin Resonance Spectroscopy

Abstract: 2,2,6,6-Tetramethyl-4-piperidone (TMPD) can react with singlet oxygen to produce the corresponding nitroxide, 2,2,6,6-tetramethyl-4-piperidone-1-oxyl (TAN), which can be detected by electron spin resonance (ESR) spectroscopy. ESR detected the formation of TAN in 5 mM riboflavin phosphate buffer, or skim milk containing 20 mM TMPD during illumination. The effects of illumination, riboflavin, and oxygen on the formation of TAN indicated that the presence of each was required for singlet oxygen formation. The pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The chemical mechanism for the formation of 2-pentylfuran from linoleic acid by singlet oxygen is shown in Figure 9. Singlet oxygen is formed by riboflavin that is in soymilk (Bradley and Min 2003). The identified 2-heptenal in Table 2 is also formed by singlet oxygen from linoleic acid (Lee and others 2003).…”
Section: Identification Of Soymilk Volatile Compounds Bymentioning
confidence: 99%
“…The chemical mechanism for the formation of 2-pentylfuran from linoleic acid by singlet oxygen is shown in Figure 9. Singlet oxygen is formed by riboflavin that is in soymilk (Bradley and Min 2003). The identified 2-heptenal in Table 2 is also formed by singlet oxygen from linoleic acid (Lee and others 2003).…”
Section: Identification Of Soymilk Volatile Compounds Bymentioning
confidence: 99%
“…Riboflavin plays important roles in the formation of light‐induced off‐flavor in dairy products through free radical generation (type I pathway) and/or singlet oxygen oxidation (type II pathway) (Edwards and Silva 2001; Boff and Min 2002). The presence of singlet oxygen in the milk stored under light was confirmed by electron spin resonance spectroscopy (Bradley and Min 2003). King and Min (1998) reported that singlet oxygen can oxidize vitamin D 2 in the light‐exposed milk with added riboflavin.…”
Section: Introductionmentioning
confidence: 99%
“…Light induced oxidation is one of the main factors limiting shelf life of milk. Exposure to visible light leads to off-flavors related to oxidation of proteins and lipids due to excitation of photosensitizers among which riboflavin has been recognized to play a major role (Bradley, Lee and Min, 2003). Riboflavin and beta-carotene are the two most prominent light absorbers in milk.…”
Section: Introductionmentioning
confidence: 99%
“…chlorophylls act primarily as type II sensitizer with the generation of the highly reactive singlet oxygen as a result (Foote, 1968). Singlet oxygen has also been detected after riboflavin induced photooxidation in skim milk (Bradley, 2003), indicating that Type I and II photoreactions are competing with each other.…”
Section: Introductionmentioning
confidence: 99%